Plasma Amyloid-beta as a Biomarker in Alzheimer's Disease: The AIBL Study of Aging - Lui, J.; Laws, S.; Li, Q.; Villemagne, V.; Ames, D.; Brown, B.; Bush, A.; De Ruyck, K.; Dromey, J.; Ellis, K.; Faux, N.; Foster, Jonathan; et al. (IOS Press, 2010)
Amyloid-β (Aβ) plays a central role in the pathogenesis of Alzheimer's disease (AD) and has been postulated as a potential biomarker for AD. However, there is a lack of consensus as to its suitability as an AD biomarker. The objective of this study was to determine the significance of plasma Aβ as an AD biomarker and its relationship with Aβ load and to determine the effect of different assay methods on the interpretation of Aβ levels. Plasma Aβ1-40, Aβ1-42, and N-terminal cleaved fragments were measured using both a commercial multiplex assay and a well-documented ELISA in 1032 individuals drawn from the well-characterized Australian Imaging, Biomarkers and Lifestyle (AIBL) study of aging. Further, Aβ levels were compared to Aβ load derived from positron-emission tomography (PET) with the Pittsburgh compound B (PiB). Lower Aβ1-42 and Aβ1-42/1-40 ratio were observed in patients with AD and inversely correlated with PiB-PET derived Aβ load. However, assay methodology significantly impacted the interpretation of data. The cross-sectional analysis of plasma Aβ isoforms suggests that they may not be sufficient per se to diagnose AD. The value of their measurement in prognosis and monitoring of AD interventions needs further study, in addition to future longitudinal comparisons together with other predictors, which will determine whether plasma Aβ has diagnostic value in a panel of biomarkers.